Some Optimal Tax Rules for International Portfolio and Direct Investment - Devereux, M (2004)
This paper explores the optimal international tax policy of a small open economy with inbound and outbound flows of both portfolio and direct investment. Only three independent conditions determine the optimal rates of six taxes, implying that there are no unique values of optimal tax rates. For example, the optimal tax rates on domestic and inbound direct investment are related through a two sector general equilibrium model. In general, optimal tax rates on inbound investment are not zero, and those on domestic and outbound investment are not equal.